(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Abstract Coronary heart disease (CAD), respiratory disease, and early-onset renal failure, which until recently were only common in high-income countries, are now the dominant source of morbidity and mortality among young Nigerian adults. However, epidemiological studies have suggested the possibility of high dietary salt intake and physical inactivity as behavioral factors that may be responsible for these growing trend. Therefore, the purpose of this study was to determine the influence of elevated salt intake and physical activity and inactivity on the pulmonary function, cardiovascular, and renal function of young Nigerian men. Methods and materials: A total of 20 subjects, comprising 10 non-exercising young men (control) and 10 exercising young men, participated in the study after obtaining an approval from the ethical committee of the animal and human research bioethics department. Lung function, oxygen saturation, blood pressure, urine volume, urine pH, and urine Na+ and K+ concentration were measured under resting conditions before and after five days of 200mmol of salt loads in both groups. The data was analyzed using the SPSS Statistics software package Version 19. The unpaired t-test was used to calculate the P-value across the groups. The paired t-test was used to calculate the p-value within the groups. Statistical significance was reached when P < 0.05. Results: Salt loading had no significant effect on the pulmonary function of the control subjects. However, salt loading worsened the pulmonary function values of the exercising subjects, with FEV1, FVC, and PEFR decreased significantly by -0.05 ± 0.05 L, -0.003 ± 0.01 L, and -20.20 ± 7.11 L/min, respectively, without affecting oxygen saturation (SPO2) and FEV1%. Salt loading caused a greater increase in the blood pressure parameters of the non-exercising subjects, with systolic pressure, diastolic pressure, mean arterial pressure, and pulse pressure significantly increased by 18.00 ± 2.04 mmHg, 11.90 ± 1.52 mmHg, 13.97 ± 1.98 mmHg, and 6.20 ± 0.24 mmHg, respectively. In summary, exercising subjects eliminate salt loads more effectively than the non-exercising subjects to reduce salt retention. This might be as a result of the trigger of several pathophysiological mechanisms that alter vital body functions such as respiratory function, renal function, and cardiovascular functions. Keywords: Oxygen Saturation, pro-inflammatory cytokines, Hyperinsulinemia, angiotensin-2, and Nitric oxide.